Morpholexicosemantics analysis of neologism on Facebook posts and threads - Joylyn Dologuin; Maria Ofelia Cristina Lood (Universitas Ahmad Dahlan, 2022)
Neologism is a word or phrase that has three classifications which are the completely newly-coined words and phrases, existing words and phrases that have new meanings and existing words or phrases with expanded meanings. This linguistic phenomenon is seen to be prevalent in Facebook posts and threads. This study was conducted to discover neologisms, their classification, word formation processes, and lexical functions. The results indicated that the word-formation processes, namely acronyms, affixations, back-formation, blending, clipping, compounding, conversion and shortening have been used and among these, affixation and compounding are the most used word-formation processes. Moreover, in its lexical functions, which are noun, verb, adjective and interjection, noun is the most used. Therefore, it is recommended that Cultural implications on the fast transmissions and influence of the creation of neologisms be further explored.